The influences of fibre parameters on the tensile and flexural response of lightweight thermoplastic kenaf fibre reinforced metal composites - Dhar Malingam, Sivakumar; Ng, Lin Feng; Lee, Chun Khoon; Sheikh Md Fadzullah, Siti Hajar; Mustafa, Zaleha; Subramonian, Sivarao (Taylor and Francis Inc., 2020)
The increasing demand for high performance and lightweight materials has stimulated the development of alternative materials, namely fiber metal laminates (FMLs). FML is a sandwich structure which is formed by bonding the metallic layers with composite as core constituent using an adhesive agent. In this study, the mechanical behavior of FMLs with the core constituents of environmental friendly kenaf bast fiber reinforced polypropylene composites bonded with aluminum skin layers was investigated. The effects of fiber compositions (50, 60, and 70 wt.%), fiber lengths (30, 60, 90 mm), and alkali treatment on the mechanical responses of FML were investigated. The overall results revealed that the increase of fiber composition and fiber length reduces the mechanical strength of FML owing to the agglomeration of natural fibers when the fiber length exceeds the critical limit. However, the chemical treated kenaf bast fiber reinforced FML showed a significant enhancement of the mechanical properties in comparison to the non-treated fiber reinforced FML owing to the improved fiber-matrix adhesion level.